Combining ability of extra-early maize inbreds derived from a cross between maize and Zea diploperennis and hybrid performance under contrasting environments - Amegbor, I.K.; Badu-Apraku, Baffour; Adu, G.B.; Adjebeng-Danquah, J.; Toyinbo, J.O. (MDPI, 2020)
Knowledge of the genetic mechanisms conditioning drought tolerance in maize is crucial to the success of hybrid breeding programs aimed at developing high-yielding cultivars under drought. The objectives of this study were to determine the combining ability of extra-early inbreds, compute the heritability of measured traits, assess the performance of inbreds in hybrid combinations and investigate the associations among traits under drought and optimal conditions. A total of 252 hybrids generated by crossing 63 inbreds to four testers, along with four commercial hybrid checks, were evaluated for 2 years under drought and rainfed conditions. General combining ability (GCA) and specific combining ability (SCA) for the traits were significant. A total of 57.1% and 53.4% of the genotypic sum of squares were attributable to GCA effects for grain yield under managed drought and rainfed conditions, respectively. Hybrids TZdEEI 91 × TZEEI 21 and TZdEEI 55 × TZEEI 13 out-yielded the best checks under drought and optimal conditions by 49.13% and 39.05%, respectively. The most promising hybrids with consistently high grain yield under drought and rainfed conditions, were TZdEEI 54 × TZEEI 13, TZdEEI 91 × TZEEI 21 and TZdEEI 55 × TZEEI 21 and should be further evaluated for possible commercial production in sub-Saharan Africa.